Grazing herbivores reduce herbaceous biomass and fire activity across African savannas - A. Tyler Karp; Sally E. Koerner; Gareth P. Hempson; Joel O. Abraham; T. Michael Anderson; William J. Bond; Deron E. Burkepile; Elizabeth N. Fillion; Jacob R. Goheen; Jennifer A. Guyton; Tyler R. Kartzinel; Duncan M. Kimuyu; et al. (Ecology Letters, 2024)
Fire and herbivory interact to alter ecosystems and carbon cycling. In savannas, herbivores can reduce fire activity by removing grass biomass, but the size of these effects and what regulates them remain uncertain. To examine grazing effects on fuels and fire regimes across African savannas, we combined data from herbivore exclosure experiments with remotely sensed data on fire activity and herbivore density. We show that, broadly across African savannas, grazing herbivores substantially reduce both herbaceous biomass and fire activity. The size of these effects was strongly associated with grazing herbivore densities, and surprisingly, was mostly consistent across different environments. A one‐zebra increase in herbivore biomass density (~100 kg/km 2 of metabolic biomass) resulted in a ~53 kg/ha reduction in standing herbaceous biomass and a ~0.43 percentage point reduction in burned area. Our results indicate that fire models can be improved by incorporating grazing effects on grass biomass.

The geography of near-shelf mixing on the east coast of South Africa - J. Pringle; D. Stretch; K. Tirok (Environmental Fluid Mechanics, 2023)

Symbiotic status alters fungal eco‐evolutionary offspring trajectories - Carlos A. Aguilar‐Trigueros; Franz‐Sebastian Krah; William K. Cornwell; Amy E. Zanne; Nerea Abrego; Ian C. Anderson; Carrie J. Andrew; Petr Baldrian; Claus Bässler; Andrew Bissett; V. Bala Chaudhary; Baodong Chen; et al. (Ecology Letters, 2023)
Despite host‐fungal symbiotic interactions being ubiquitous in all ecosystems, understanding how symbiosis has shaped the ecology and evolution of fungal spores that are involved in dispersal and colonization of their hosts has been ignored in life‐history studies. We assembled a spore morphology database covering over 26,000 species of free‐living to symbiotic fungi of plants, insects and humans and found more than eight orders of variation in spore size. Evolutionary transitions in symbiotic status correlated with shifts in spore size, but the strength of this effect varied widely among phyla. Symbiotic status explained more variation than climatic variables in the current distribution of spore sizes of plant‐associated fungi at a global scale while the dispersal potential of their spores is more restricted compared to free‐living fungi. Our work advances life‐history theory by highlighting how the interaction between symbiosis and offspring morphology shapes the reproductive and dispersal strategies among living forms.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Portable X-ray fluorescence (pXRF) analysis of heavy metal contamination in church graveyards with contrasting soil types - Charles Madden; Jamie K. Pringle; Adam J. Jeffery; Kristopher D. Wisniewski; Vivienne Heaton; Ian W. Oliver; Helen Glanville; Ian G. Stimpson; Henry C. Dick; Madeleine Eeley; Jonathan Goodwin (Environmental Science and Pollution Research, 2022)
Human remains have been interred in burial grounds since historic times. Although the re-use of graveyards differs from one country, region or time period to another, over time, graveyard soil may become contaminated or enriched with heavy metal elements. This paper presents heavy metal element soil analysis from two UK church graveyard study sites with contrasting necrosols, but similar burial densities and known burial ages dating back to the sixteenth century and some possibly older than 1,000 years. Portable X-ray fluorescence element laboratory-based analyses were undertaken on surface and near-surface soil pellets. Results show elevated levels of Fe, Pb, Mn, Cr, Cu, Zn and Ca in both necrosols when compared with background values. Element concentration anomalies remained consistently higher than background samples down to 2 m, but reduced with distance away from church buildings. Element concentration anomalies are higher in the clay-rich necrosol than in sandy necrosol. Study result implications suggest that long-used necrosols are likely to be more contaminated with heavy metal elements than similar soil outside graveyards with implications for burial grounds management, adjacent populations and where burial grounds have been deconsecrated and turned to residential dwellings.

Interactive effects of multiple stressors vary with consumer interactions, stressor dynamics and magnitude - Mischa P. Turschwell; Sean R. Connolly; Ralf B. Schäfer; Frederik De Laender; Max D. Campbell; Chrystal Mantyka‐Pringle; Michelle C. Jackson; Mira Kattwinkel; Michael Sievers; Roman Ashauer; Isabelle M. Côté; Rod M. Connolly; et al. (Ecology Letters, 2022)
Predicting the impacts of multiple stressors is important for informing ecosystem management but is impeded by a lack of a general framework for predicting whether stressors interact synergistically, additively or antagonistically. Here, we use process‐based models to study how interactions generalise across three levels of biological organisation (physiological, population and consumer‐resource) for a two‐stressor experiment on a seagrass model system. We found that the same underlying processes could result in synergistic, additive or antagonistic interactions, with interaction type depending on initial conditions, experiment duration, stressor dynamics and consumer presence. Our results help explain why meta‐analyses of multiple stressor experimental results have struggled to identify predictors of consistently non‐additive interactions in the natural environment. Experiments run over extended temporal scales, with treatments across gradients of stressor magnitude, are needed to identify the processes that underpin how stressors interact and provide useful predictions to management.

Mineral distribution and provenance of heavy mineral sands (zircon, ilmenite, rutile) deposits from the NW Murray Basin, far western NSW, Australia - P. Poon; I. T. Graham; E. A. C. Liepa; D. R. Cohen; I. J. Pringle; D. A. Burkett; K. Privat (Australian Journal of Earth Sciences, 2020)

Invasion of freshwater ecosystems is promoted by network connectivity to hotspots of human activity - Daniel S. Chapman; Iain D. M. Gunn; Henrietta E. K. Pringle; Gavin M. Siriwardena; Philip Taylor; Stephen J. Thackeray; Nigel J. Willby; Laurence Carvalho (Global Ecology and Biogeography, 2020)
Aim Hotspots of human activity are focal points for ecosystem disturbance and non‐native introduction, from which invading populations disperse and spread. As such, connectivity to locations used by humans may influence the likelihood of invasion. Moreover, connectivity in freshwater ecosystems may follow the hydrological network. Here we tested whether multiple forms of connectivity to human recreational activities promotes biological invasion of freshwater ecosystems. Location England, UK. Time period 1990–2018. Major taxa studied One hundred and twenty‐six non‐native freshwater birds, crustaceans, fish, molluscs and plants. Methods Machine learning was used to predict spatial gradients in human recreation and two high risk activities for invasion (fishing and water sports). Connectivity indices were developed for each activity, in which human influence decayed from activity hotspots according to Euclidean distance (spatial connectivity) or hydrological network distance (downstream, upstream and along‐channel connectivity). Generalized linear mixed models identified the connectivity type most associated to invasive species richness of each group, while controlling for other anthropogenic and environmental drivers. Results Connectivity to humans generally had stronger positive effects on invasion than all other drivers except recording effort. Recreation had stronger influence than urban land cover, and for most groups high risk activities had stronger effects than general recreation. Downstream human connectivity was most important for invasion by most of the groups, potentially reflecting predominantly hydrological dispersal. An exception was birds, for which spatial connectivity was most important, possibly because of overland dispersal capacity. Main conclusions These findings support the hypothesis that freshwater invasion is partly determined by an interaction between human activity and species dispersal in the hydrological network. By comparing alternative connectivity types for different human activities, our approach could enable robust inference of specific pathways and spread mechanisms associated with particular taxa. This would provide evidence to support better prioritization of surveillance and management for invasive non‐native species.

Changes in Stream Primary Producer Communities Resulting from Large-Scale Catastrophic Amphibian Declines: Can Small-Scale Experiments Predict Effects of Tadpole Loss? - Scott Connelly; Catherine M. Pringle; Rebecca J. Bixby; Roberto Brenes; Matt R. Whiles; Karen R. Lips; Susan Kilham; Alexander D. Huryn (Ecosystems, 2008)

Preliminary x-ray characterization of authentic providence virus and attempts to express its coat protein gene in recombinant baculovirus - D. J. Taylor; J. A. Speir; V. Reddy; G. Cingolani; F. M. Pringle; L. A. Ball; J. E. Johnson (Archives of Virology, 2006)

Larval lobster ( Homarus americanus ) distribution and drift in the vicinity of the Gulf of Maine offshore banks and their probable origins - G. C. HARDING; K. F. DRINKWATER; C. G. HANNAH; J. D. PRINGLE; J. PRENA; J. W. LODER; S. PEARRE; W. P. VASS (Fisheries Oceanography, 2005)
Surveys for lobster larvae in offshore waters of the north‐eastern Gulf of Maine in 1983, 1987 and 1989 confirm that local hatching occurs mainly at depths

The effects of stressors on the dynamics of Bonamia exitiosus Hine, Cochennec‐Laureau & Berthe, infections in flat oysters Ostrea chilensis (Philippi) - P M Hine; B K Diggles; M J D Parsons; A Pringle; B Bull (Journal of Fish Diseases, 2002)
Oysters, Ostrea chilensis , infected with Bonamia exitiosus were held under stressful conditions for 14 days, and then under normal conditions for 3.5 months, to determine the affects of stress on B.exitiosus infection levels. The stressors used were (1) air exposure for 8 h daily; (2) hot water (25–26 °C), or (3) cold water (7 °C) for 1 h daily; (4) hyposaline (15‰), or (5) hypersaline (39–40‰) water; (6) starvation in filtered sea water; and (7) vigorous stirring four times a day. A control tank held oysters in static sea water, which was changed daily. Oysters were also (8) kept in a trough among heavily infected oysters (trough exposure), or (9) in a trough without other oysters (control), for 4 months. Oysters in hyposaline conditions all died within 3 weeks, but this was apparently unrelated to Bonamia infection. Otherwise, cumulative mortalities were highest in trough exposure, cold, hypersaline and hot treatments. There was a significant difference in prevalence between treatments, and the stir, hot, cold, hypersalinity and trough exposure treatments had significantly higher intensities of infection than controls. The mean intensity of Bonamia infection was significantly higher among female and spent oysters than in male and hermaphrodite oysters.

Landscape variation in phosphorus concentration and effects on detritus‐based tropical streams - Amy D. Rosemond; Catherine M. Pringle; Alonso Ramírez; Michael J. Paul; Judy L. Meyer (Limnology and Oceanography, 2002)
Landscape‐scale variation in streamwater phosphorus (P) concentration can affect aquatic food webs. Such variation occurs naturally in streams at La Selva Biological Station in Costa Rica due to spatially variable inputs of geothermally modified groundwater. We examined effects of this gradient on detrital food web components at 16 stream sites. The Michaelis‐Menten model provided a good fit of the relationship between soluble reactive phosphorus (SRP) and leaf decay rate, fungal biomass, and invertebrate biomass, indicating that these variables were controlled by P concentration and that half‐saturation constants were relatively low (7—13 µg L −2 1 SRP). In a subsequent short‐term (3 week) whole‐stream P enrichment study, we found no effect of P addition on leaf decay rate or on biomass or density of invertebrates. However, laboratory tests of P, N, and Ca concentrations on mass loss of leaves showed detectable stimulation by both N and P after 3 weeks. A fourth study assessed the relative contribution of invertebrate consumption versus P concentration in determining decay rates among streams. The majority of variation was due to P concentration (71%), compared to effects of invertebrates (3%) or invertebrate × P interactions (14%). Overall, we found that a landscape‐scale natural gradient in P concentration influenced decay rates of organic matter and biomass of consumers, providing evidence that benthic detrital food webs can be limited from the bottom up by nutrients. Microbial processes appeared to be most important in driving differences in organic matter decay among sites, but invertebrates also contributed to elevated decay rates at high‐P sites.